Culture, colour connotations and the effects of simultaneous bilingualism on perception - Tan, Xanthe (Nanyang Technological University, 2020)
‘White lies’, the ‘black market’ and ‘to have a green thumb’, what do these metaphors have in common? Colours play a huge part in everyone’s lives. Meaningful use of colours is commonplace – from marketing tactics to the clothes we wear. The connotation of colours reflects beliefs of a particular culture; this association could suggest similarities between cultures – e.g. green is associated with envy by the French, Italian, and English native speakers, while German speakers associate it with yellow (Dolan, Volkova, Wilson, 2012), or differences. But how does the language one speaks influence our perception of what a colour connotes? The study focuses on the relation between language and culture, through the means of colour connotations. 50 English Mandarin (EM) bilinguals were tasked to complete a three-part questionnaire investigating perceived colour senses. Results showed the effects of language dominance and linguistic relativity and ethnic affirmation. The present work provides researchers with an insight into the link between language and culture. Further studies on the subject through other research methods such as the Implicit Association Test (IAT), and the recruitment of individuals with similar fluency levels in their non-dominant language, would provide a clearer, more accurate, view on the topic.